Applying of Hypertext to Promote EFL Students’ Reading Comprehension - Tatu Munawaroh (Journal of English Education Studies, 2019)
This study investigated applying of hypertext to promote EFL for students to improve reading comprehension. The objective of this study is to find out the implementation of hypertext and to what extent the use of hypertext can improve students’ reading comprehension. This study is applying classroom action research which was conducted at one of senior high school in Pandeglang and predicated by 27 second grade students of senior high school. For analysis of the data, this study used qualitative approach supported with observation, students’ test, questionnaire, and interview. This study showed applying of hypertext in teaching and learning process was successful. The data gained from students’ test showed that the applying of hypertext to promote EFL can improve students’ reading comprehension. The mean of students score in the third cycle was 73.92 with twenty one students achieved score above minimum completion score or KKM (70). In addition, most students agree that applying of hypertext can improve their reading comprehension. For the finding it is recommended for further studies that the applying of hypertext can be implemented in teaching English lesson to improve the students’ reading comprehension.